2019
DOI: 10.1111/cei.13406
|View full text |Cite|
|
Sign up to set email alerts
|

Cisplatin-mediated down-regulation of miR-145 contributes to up-regulation of PD-L1 via the c-Myc transcription factor in cisplatin-resistant ovarian carcinoma cells

Abstract: Summary Immune tolerance is one of the leading causes of chemotherapy resistance in carcinoma cases. Studies have shown that programmed cell death ligand‐1 (PD‐L1), an inhibitory molecule expressed by cancer cells, plays a significant role in immune tolerance through the induction of T cell dysfunction. The results of our RNA sequencing in previous studies revealed that microRNA‐145 (miR‐145), which is known to be down‐regulated by cisplatin in cisplatin‐resistant ovarian cancer cells, also represses gene PD‐L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Programmed death‐ligand 1 (PD‐L1) is an inhibitory molecule expressed by cancer cells, which plays a significant role in immune tolerance through the induction of T cell dysfunction. The MiR‐145/c‐Myc/PD‐L1 axis contributed to cisplatin resistance in ovarian cancer 10 …”
Section: Mir‐145 In Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Programmed death‐ligand 1 (PD‐L1) is an inhibitory molecule expressed by cancer cells, which plays a significant role in immune tolerance through the induction of T cell dysfunction. The MiR‐145/c‐Myc/PD‐L1 axis contributed to cisplatin resistance in ovarian cancer 10 …”
Section: Mir‐145 In Drug Resistancementioning
confidence: 99%
“…Researchers are currently attempting to explore the target genes of miR‐145 and their signaling pathways involved in altering therapeutic response, which is significant for the development of miRNA‐related therapies. Strikingly, various research has disclosed that miR‐145 acts in reversion of therapeutic resistance in multiple tumors, including lung cancer, 3‐6 esophageal squamous cell carcinoma (ESCC), 7‐9 ovarian carcinoma, 10,11 glioma, 12,13 hepatocellular carcinoma (HCC), 14‐16 breast cancer, 17 colorectal cancer (CRC) 18‐21 prostate cancer, 22,23 bladder cancer, 24 gastric cancer (GC), 25,26 pancreatic adenocarcinoma 27 and cervical cancer 28,29 …”
Section: Introductionmentioning
confidence: 99%
“…22,23 According to earlier studies, miR-145 mostly acts as a tumor suppressor in malignant tumors. 24,25 Our study results demonstrated that miR-145 was lowly expressed in HCC, and was linked to high clinical staging and lymph node metastasis. In addition, follow-up for prognosis revealed that low miR-145 expression was linked to the unfavorable prognosis of the patients.…”
Section: Discussionmentioning
confidence: 70%
“…Our observations were consistent with previous studies and confirmed the involvement of TUG1 in the ceRNA mechanism. Notably, there have been several other miRNAs negatively regulated by TUG1 in cancers (60)(61)(62), among which quite a few miRNAs have been reported to have a tumor suppressive role in OC (63)(64)(65). TUG1 could sponge more than one miRNA in OC and affect the development of OC through different signaling pathways.…”
Section: Discussionmentioning
confidence: 99%